Mr mcgillicuddy's clocks - Best, Elizabeth (Nelson Australia Melbourne, 1994)
Pasquale's Gift is a novel by Paul Russell that explores the emotional and psychological complexities of relationships and self-discovery. The story follows the life of protagonist Pasquale, a deeply introspective man, as he navigates love, loss, and identity. Set in Italy, the novel delves into themes of longing, memory, and the human desire for connection, while also touching on cultural and familial expectations. Pasquale's journey leads him to confront his past and embrace the present, offering a poignant reflection on the nature of personal transformation.